Mounting the Antelope: How the Early American Wild Became a Document - Adler, Melissa (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This paper troubles and historizes the symbolic use of the antelope in the field of library and information science by examining correspondence during the Lewis and Clark expedition in the nineteenth century. It shows how taking the antelope from the wild, naming and classifying the animal, and mounting it for display in a museum were part of a national literacy education program in the early United States. The “American antelope” was observed and killed during the expedition, and Thomas Jefferson, serving as both president of the United States and president of the American Philosophical Society, was intimately engaged in conversations about what to call the animal. Charles Willson Peale mounted an antelope that had been sent from the expedition and classified it according to a Linnean system. This moment is instructive for understanding how information and wild animals became things in processes of settler colonialism and empire expansion.